2008 IEEE Nuclear Science Symposium Conference Record 2008
DOI: 10.1109/nssmic.2008.4775175
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of a novel energy-resolved photon-counting gamma ray detector

Abstract: In this paper, we present the design and preliminary performance evaluation of a novel energyresolved photon-counting (ERPC) detector for gamma ray imaging applications. The prototype ERPC detector has an active area of 4.4 cm × 4.4 cm, which is pixelated into 128 × 128 square pixels with a pitch size of 350 µm × 350µm. The current detector consists of multiple detector hybrids, each with a CdTe crystal of 1.1 cm × 2.2 cm × 1 mm, bump-bonded onto a customdesigned application-specific integrated circuit (ASIC).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…The designed anode is bump bonded to an application specific integrated circuit (ASIC) based on a modification of the MGC700T2 design developed by Ajat Oy Ltd [41]. This work further builds on the benchtop CdTe detector design reported on by Meng et al by enabling the HPWF readout method [42]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The designed anode is bump bonded to an application specific integrated circuit (ASIC) based on a modification of the MGC700T2 design developed by Ajat Oy Ltd [41]. This work further builds on the benchtop CdTe detector design reported on by Meng et al by enabling the HPWF readout method [42]. …”
Section: Methodsmentioning
confidence: 99%
“…Each hybrid is composed of a CdTe crystal with a pixelated anode bump-bonded to a 2048 (32 × 64)-channel ASIC to read out the anode pixels. Each pixelated element is 350 μm × 350 μm in size [42]. …”
Section: Methodsmentioning
confidence: 99%
“…The pixel pitch size is 0.35mm × 0.35mm and the intrinsic energy resolution of the ERPC detector is around 3kev at 140kev events. We have previously reported the performance of the first generation ERPC ASICs in [3]. The ASICs in the Gen-II ERPC detectors allow for a much lower low energy threshold, and incorporates three gain levels for handle different gamma ray energies.…”
Section: Methodsmentioning
confidence: 99%
“…Meier et al have reported an MR-compatible SPECT system based on CZT detectors [1] and an MRSPECT system is developed by Hamamura et al [2]. We have previously developed a sub-500μm resolution prototype MR compatible system based on the first generation energy-resolved photon-counting (ERPC) CdTe detectors [3-4]. It offers spatial resolution of 350μm and energy resolution of 3-4kev.…”
Section: Introductionmentioning
confidence: 99%
“…These detectors have either been based on direct detection of gamma rays in semiconductor material (e.g. Matteson et al (1997), Barber (1999), He et al (1999), Wagenaar et al (2003), Kataoka et al (2005), Ponchut et al (2005), Accorsi et al (2008), Meng et al (2009b), Peterson et al (2009) and Russo et al (2009)), scintillation detection employing high-resolution position-sensitive light sensors (e.g. Menard et al (1998), Fiorini et al (2003), Lees et al (2003), Beekman and De Vree (2005), Nagarkar et al (2006), Miller et al (2006), Soesbe et al (2007) and Meng and Fu (2008)) or even a combination of both (Miyata et al 2004).…”
Section: Introductionmentioning
confidence: 99%